Pregnancy as a susceptible state for thrombotic microangiopathies - Frimat, Marie; Gnemmi, Viviane; Stichelbout, Morgane; Provôt, François; Fakhouri, Fadi (Frontiers in Medicine, 2024)
Pregnancy and the postpartum period represent phases of heightened vulnerability to thrombotic microangiopathies (TMAs), as evidenced by distinct patterns of pregnancy-specific TMAs (e.g., preeclampsia, HELLP syndrome), as well as a higher incidence of nonspecific TMAs, such as thrombotic thrombocytopenic purpura or hemolytic uremic syndrome, during pregnancy. Significant strides have been taken in understanding the underlying mechanisms of these disorders in the past 40 years. This progress has involved the identification of pivotal factors contributing to TMAs, such as the complement system, ADAMTS13, and the soluble VEGF receptor Flt1. Regardless of the specific causal factor (which is not generally unique in relation to the usual multifactorial origin of TMAs), the endothelial cell stands as a central player in the pathophysiology of TMAs. Pregnancy has a major impact on the physiology of the endothelium. Besides to the development of placenta and its vascular consequences, pregnancy modifies the characteristics of the women’s microvascular endothelium and tends to render it more prone to thrombosis. This review aims to delineate the distinct features of pregnancy-related TMAs and explore the contributing mechanisms that lead to this increased susceptibility, particularly influenced by the “gravid endothelium.” Furthermore, we will discuss the potential contribution of histopathological studies in facilitating the etiological diagnosis of pregnancy-related TMAs.